Analysis of The Development of Terrorist Groups In The Jurisdiction of The Sidoarjo Police Office - Yosep Putra Sudibyo; Alif Bryan Pradana Kusuma; Andi Gibran Gani Mandica (Akademi Kepolisian Republik Indonesia, 2024)
The study